It's all about the T: transcription termination in archaea. (19th February 2019) - Maier, Lisa-Katharina; Marchfelder, Anita
Abstract : One of the most fundamental biological processes driving all life on earth is transcription. The, at first glance, relatively simple cycle is divided into three stages: initiation at the promoter site, elongation throughout the open reading frame, and finally termination and product release at the terminator. In all three processes, motifs of the template DNA and protein factors of the transcription machinery including the multisubunit polymerase itself as well as a broad range of associated transcription factors work together and mutually influence each other. Despite several decades of research, this interplay holds delicate mechanistic and structural details as well as interconnections yet to be explored. One of the surprising characteristics of archaeal biology is the use of eukaryotic-like information processing systems against a backdrop of a bacterial-like genome. Archaeal genomes usually comprise main chromosomes alongside chromosomal plasmids, and the genetic information is encoded in single transcriptional units as well as in multicistronic operons alike their bacterial counterparts. Moreover, archaeal genomes are densely packed and this necessitates a tight regulation of transcription and especially assured termination events in order to prevent read-through into downstream coding regions and the accumulation of antisense transcripts.